Evaluation and Improvement of Oncologists’ Adherence to NCCN Guideline for Prevent and Treatment of Cancer Associated Venous Thromboembolism - Naeemah, Ghufran Hassoun; AL. Ameen, Ayad Ali Hussein (Journal of Contemporary Medical Sciences, 2024)
Objective: the aim of this study is asses the adherence of physician to NCCN guideline recommended anticoagulant therapy in patient with cancer associated venous thromboembolism. Method: study was designed with two phases an observational phase and an interventional prospective phase with the educational program, was conducted at Middle Euphrates cancer center /An-Najaf governorate/Iraq. Ten oncologists who agreed to participate in the study. Used validated questionnaire include (25 items) where distributed to 10 oncologists who were working at the Middle Euphrates cancer center then all questionnaires were collected from participated oncologists over two months. Subsequently, an educational part including a lecture and posters was submitted in cancer center to in raising awareness of seriousness of this disease and how prevention and treatment. Results: The overall mean total score of oncologists for prevention and management of cancer associated VTE (out of 25 items) of all questionnaire parts was remarkably increased from (0.54) to (0.72) after the intervention therefore the level of oncologist's adherence to NCCN guideline improved to 70% with large effect size (1.04). Conclusion: According to the final evaluation of responses of oncologists showed improvement in adherence toward the NCCN guideline. In addition, there were several barriers that mainly reduce the adherence like sever side effect, increase cost and Lack of awareness of guidelines.